Crystal structure of 1,1,3-trimethyl-2-(2-(2,2,6-trimethyl-cyclohexyl)ethyl) cyclohexane, C20H34 - Zukerman-Schpector, Julio (2007)
C20H34, monoclinic, P12(1)/n1 (no. 14), a = 10.647(l) angstrom, b = 6.6844(9) angstrom, c = 11.723(1) angstrom, beta = 99.75(1)degrees, V = 822.3 angstrom(3) Z = 2, R-gt(F) = 0.043, wR(ref)(F-2) = 0.110, T = 93 K.